Impact of Gender Responsive Budget on Local Development in Nepal - Sijapati, Dipendra Bikram (Patan Prospective Journal, 2022)
This article based on Gender responsive aims at raising awareness of the gendered impacts of local development budget and to make governments accountable for ensuring gender equality and women’s rights. This paper to explore the gender response budget in local level government and examines the gender development issues at the local level. The descriptive and analytical technique are used to explain the gender sensitivity of policies, planning and programming, and budgeting process of the selected two districts in five different local government in Nepal. The results clearly show that merely preparing GRB and strategies does not solve the problem of inequality. Therefore, translating gender mainstreaming into actual action requires a re-examination of the policies, programs and planning/budgeting process from the gender perspectives. Due to the lack of gender needs before planning and allocating gender budgets, the implementation of the Gender friendly budget is fully depends on the service provider’s strength, interest in skill development, and capacity building to implement the local development programs.